Women’s Satisfaction and Its Associated Factors with Antenatal Care Services at Public Health Facilities: A Cross-Sectional Study - Ayalew MM; Nebeb GT; Bizuneh MM; Dagne AH (Dove Medical Press, 2021)
Mequannent Melaku Ayalew,1 Gebeyehu Tsega Nebeb,1 Mekonnen Melikie Bizuneh,1 Asrat Hailu Dagne2 1School of Public Health, Bahir Dar University, Bahir Dar, Amhara Region, Ethiopia; 2Department of Midwifery, Debre Tabor University, Debre Tabor, Amhara Region, EthiopiaCorrespondence: Asrat Hailu Dagne Tel +251963724991Email 1221Asrat@gmail.comBackground: Regular monitoring and evaluation improves the quality of health services. Client satisfaction is an indicator of the quality of a health service. Poor maternal satisfaction with antenatal care services has negative outcomes. Currently, women’s satisfaction with antenatal care services is below standard in low-income countries such as Ethiopia. Therefore, this study aimed to assess women’s satisfaction and its associated factors with antenatal care services.Methods: A facility-based cross-sectional study was conducted from September 23 to October 23, 2019. A total of 405 women were involved in the study. A systematic random sampling technique was used. The data were coded manually and checked visually for completeness. The data were entered using Epi Info version 7 and exported to SPSS version 20 for analysis. Descriptive statistic was computed. Thechi-squared test was performed and factors associated with women’s satisfaction with antenatal care services were selected for multiple logistic regression at a probability value (p-value) of < 0.2 in the chi-squared analysis. Statistically significant associated factors were identified at a p-value of ≤ 0.05, and with adjusted odds ratios and 95% confidence intervals.Results: Among 405 participants, 53.8% (95% CI=48.7– 59%) of women were satisfied with the antenatal care services. Age of mothers (AOR=6.04, 95% CI=2.3– 15.9), advice on danger signs in pregnancy (AOR=4.53, 95% CI=2.7– 7.52), previous antenatal care visits (AOR=3.8, 95% CI=2.0– 7.52), respectful maternity care (AOR=8.2, 95% CI=3.3– 20.4), and planned pregnancy (AOR=2.8, 95% CI=1.6– 4.8) were statistically significantly associated with women’s satisfaction with antenatal care services.Conclusion: About half of the participants were satisfied with the antenatal care services. Age of participants, respectful maternity care, advice on danger signs in pregnancy, previous antenatal care visits, and planned pregnancy were found to be predictors of women’s satisfaction with antenatal care services.Keywords: satisfaction, respectful maternity care, antenatal care